Strategy for selling dreams: The Portuguese luxury world - Sousa, Ana Sofia Faustino Marques de (2021)
The growth of the luxury market in the last decades and the globalization, through digitization, has led to the emerge of more luxury brands in Portugal, that have brought with them new business models thoroughly connected with the digital. It also led the established portuguese luxury brands to rethink their business models, thus leading to a profound rethinking of Portuguese luxury business models. The objective of this dissertation is to characterize the portuguese luxury strategy, via his luxury business model. Through that luxury business model establish a comparative model for Portugal with other geographies and use it to provide recommendations and suggestions for the most favorable luxury business models, attending to the new trends on the matter. This investigation presents and discusses the data collected for several portuguese luxury brands, in the segment of personal goods, such as Pé de Chumbo, Josefinas and Carlos Santos Shoes. The main characteristics of the business model identified are the international exposure of the brand, the corporate environment, and the brand strategy in terms of products, distribution and communication. Among the results found during this investigation, it is noteworthy that portuguese luxury brands differ essentially in craftmanship and savoir-faire and that this characteristic adds them in scarcity and consequently in exclusivity, one of the main attributes pursued by luxury consumers. On the other hand, the use of social media and online stores for communication and distribution, respectively, allows them flexibility and facilitate the internationalization.